New educational approach for the sustainability of natural forest capital: review, analysis and conceptual contributions on the natural capital of the Romerillo forest - Bonilla De Gracia, Jesús A. (2024)
Universidad Nacional Agraria La Molina. Facultad de Economía y Planificación. Departamento Académico de Economía y Planificación